RANCANG BANGUN ONLINE SHOP “ROLLAS STORE” BERBASIS WEB DENGAN TEHNIK SLIDESHOW RESPONSIVE - Mutiara Saputra, Henry; Saefurrohman, Saefurrohman (Information Technology and Telematics, 2018)
ABSTRACT Rollas Store is one of the companies engaged in the sale of clothes in Semarang. But now the business process run by Rollas Store is still manual. Buyers must see the catalog in Rollas Store and the information provided is only by word of mouth or using existing social networks. An online shop will help businesses that are already running, because an item offered can be accessed by anyone, anytime and anywhere. To facilitate customers in viewing the goods catalog in Rollas Store online shop, the slide show method is used. The slide show method will display items and details of items that Rollas Store sells automatically. System development method used in this research is waterfall which consists of analysis, design with UML, coding using PHP and MySQL, testing. The final result of this study is an online shop on web-based Rollas Store that can be accessed by anyone who uses internet media so that it can attract customers to buy Rollas Store items using the slide show method.